U.S. Defense dollars for computer science plunge [computer science research]. - Kumagai, J. (IEEE spectrum)
This paper reports on how the US Defense Department has been slowly reducing its annual budget for computer science research in favor of near-term projects with a strictly military focus. While researchers can seek funding from the National Science Foundation (NSF), their grants tend to be smaller than compared to the Defense Advanced Research Projects Agency (DARPA), which appears to favor industry laboratories over the academia. Despite denials from DARPA officials, those familiar with budgetary decision making within the Pentagon say that there in fact has been a shift at DARPA, driven in large part by the country's ongoing conflicts in Iraq and Afghanistan. There are also those who believe that the IT industry, rather than the federal government, should sponsor its own research.